PHYTOCHEMICAL SCREENING AND FREE RADICAL–SCAVENGING ACTIVITY OF ORTHOSIPHON STAMINEUS (CAT WHISKERS) LEAVES - Sari, Indah Puspita (Indonesian Journal of Cosmetics, 2023)
Orthosiphon stamineus, commonly known as "Cat's Whiskers" or "Java Tea," is a medicinal herb found in Southeast Asian nations, known for its historical use in treating various ailments. This study aimed to extract and analyze the phytochemical composition of Orthosiphon stamineus using the maceration technique, followed by an assessment of its antioxidant potential through the DPPH assay. The phytochemical screening revealed the presence of flavonoids, saponins, and tannins, which align with prior research. Notably, the plant contains polyphenolic compounds, with flavonoids like sinensetin and eupatorin, as well as terpenoids, including labdane diterpenes. Essential oils, mainly composed of monoterpenes and sesquiterpenes, were also identified. While alkaloids like orthosiphol C have been reported, they were not detected in this research. The DPPH assay demonstrated that the extract exhibited increasing inhibitory activity against DPPH radicals with higher concentrations, indicating its potential as a natural antioxidant source. The presence of rosmarinic acid and flavonoids suggests potential antioxidant effects that may be explored further. Overall, this study provides insights into the phytochemical profile of Orthosiphon stamineus and its potential benefits, particularly in skin anti-aging. Further research is needed to fully understand the pharmacological significance of its compounds.